The Role of Motivational Strategy and Leadership in Improving Service Quality in Hospitals - Usman, Bahtiar; Anggiani, Sarfilianty; Hariyadi, Hariyadi (Politeknik Siber Cerdika Internasional, 2025)
This study aims to analyze the effect of Motivation Strategy and Leadership on Service Quality in hospitals, with Job Satisfaction as a mediating variable in the influence between Motivation Strategy, Transformational Leadership, and Transactional Leadership on Service Quality of medical personnel. This study uses a quantitative approach with non-probability sampling method and purposive sampling technique. The unit of analysis is medical personnel at military Hospital, with a sample size of 200 respondents. Data collection was done through questionnaires, and data analysis using Structural Equation Modeling (SEM) method with SMART PLS version 3.0. The results showed that of the 7 direct influence hypotheses, 4 hypotheses were supported, and 3 hypotheses were not supported. Meanwhile, of the 3 indirect effect hypotheses, 2 hypotheses are supported, and 1 hypothesis is not supported. Job Satisfaction is proven to be a mediating variable that strengthens the influence between Motivation Strategy, Leadership (Transformational and Transactional), and Service Quality. This study provides theoretical contributions in the field of strategic health management, as well as practical implications, such as the importance of leadership training, development of individual-based motivation strategies, and improving work environment support for medical personnel. The limitation of the study lies in the cross-sectional approach, which does not allow analysis of long-term changes. The originality of this study lies in the integration of Leadership (Transformational and Transactional) and Motivation Strategy variables in the context of a military hospital, by highlighting Job Satisfaction as a mediating variable. This study fills the gap of previous research by analyzing more deeply the influence between Leadership, Motivation, and Service Quality in the military hospital environment.